Fresh fruit bunch solid wastes: processing, conversion and utilisation nexus in Nigeria. - Anyaoha, Kelechi Ezenwa (Cranfield University, 2018)
The oil palm fresh fruit bunch (FFB) solid wastes, which include the empty fruit bunch (EFB), mesocarp fibre (MF), and palm kernel shell (PKS) are generated during the production of palm oil. The utilisation of the ash resulting from combustion or gasification of the FFB solid wastes for soil improvement and crop yield especially cassava is a challenge in the management of the FFB solid wastes. This study is aimed at understanding the relationship between the processing of the FFB in Nigeria, thermal conversion of the FFB solid wastes, and the utilisation of the ash for soil improvement and cassava yield. The industrial, small-scale, and traditional routes of the FFB processing in Nigeria were investigated to determine the losses associated with each. Secondly, the effects of the co-firing of the EFB with MF and PKS were investigated. Finally, ash from the FFB solid wastes was applied on soil at different levels (0, 40, 80, and 160 tonnes/ha) and feedstock compositions to determine the effects on soil nutrient contents and cassava tuber yield. In the industrial route, 29, 18, 75, and 27 kg of CPO, PK, MF, and PKS were lost for every 1000 kg of the FFB processed more than in the small-scale and traditional routes, respectively. The use of 40 tonnes/ha, and 80 tonnes/ha treatments resulted in 427 % and 341 % more cassava tuber yield than the control plot, respectively. The ash of the EFB, MF and PKS feedstock resulted in more cassava tuber yield of approximately 6 tonnes/ha than that of only MFand PKS feedstock (3 tonnes/ha). The thesis has demonstrated that the use of ash from the FFB solid wastes for agricultural purposes is related to the thermal conversion and the processing of the FFB. The feedstock of the equal mixture of EFB, MF and PKS is more valuable for the generation of ash useful as soil amendment and in cassava production providing evidence for the co-firing of the EFB, MF and PKS and improved efficiency of the FFB processing.
Keywords: Oil palm; empty fruit bunch; mesocarp fibre; palm kernel shell; soil; ash